2017
DOI: 10.4103/0973-1075.204232
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric end-of-life care barriers and facilitators: Perception of nursing professionals in Jordan

Abstract: Introduction:End-of-life care is a critical issue for pediatric population with terminal illness to ensure the best possible quality of care for them and their families. A survey was conducted to identify the barriers and facilitators to provide pediatric end-of-life care.Methods:A descriptive cross-sectional study was conducted at three tertiary centers providing end-of-life care in Jordan. Two hundred critical care nurses were surveyed (response rate 93%).Results:Nurses reported moderate level of experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…Despite increasing support, the quality of palliative care at the end of life in the ICU has shown little or no improvement over time (DeCato et al, ; Penrod et al, ). Several studies from around the world have reported significant barriers that block the integration of palliative care into the ICU (Aslakson et al, ; Azzizadeh Forouzi et al, ; Friedenberg et al, ; Khraisat et al, ). These barriers include inadequate training of the staff in palliative care, ICU cultural norms that encourage continuation of therapy at all costs and resistance from family members to change the goals of therapy because of unrealistic expectations (Aslakson et al, ; Azzizadeh Forouzi et al, ; Friedenberg et al, ; Holms et al, ; Zante et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing support, the quality of palliative care at the end of life in the ICU has shown little or no improvement over time (DeCato et al, ; Penrod et al, ). Several studies from around the world have reported significant barriers that block the integration of palliative care into the ICU (Aslakson et al, ; Azzizadeh Forouzi et al, ; Friedenberg et al, ; Khraisat et al, ). These barriers include inadequate training of the staff in palliative care, ICU cultural norms that encourage continuation of therapy at all costs and resistance from family members to change the goals of therapy because of unrealistic expectations (Aslakson et al, ; Azzizadeh Forouzi et al, ; Friedenberg et al, ; Holms et al, ; Zante et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Difficulty with communication between health care professionals and patient is difficult when caring for children, and it already began when a serious diagnosis need to be discussed and bad news delivered to a child and his or her parents [13,4]. In study conducted by Esmaili et al (2018), a lack of communication between staff and terminally ill patients can be caused by the cultural norms that dictated these communication patterns which does not allow staff to mention dying, even when that is the case [14], Moreover, deal with angry family member situation might also be a barrier for nurses to provide pediatric EOLC since nurses must have time to listen when family need to express their feelings, to provide comfort and talk openly and honestly about grief [15]. Barriers in this communication may occur when physicians are evasive and avoid the family [16].…”
Section: Communication and Language Barriersmentioning
confidence: 99%
“…In several studies, nurses reported that the health care professional related barrier to provide pediatric end-of-life care was multiple physicians or health care professionals do not have the same perspectives about the direction care or treatment plans [15,18,19].…”
Section: Barriers In Interdisciplinary Teammentioning
confidence: 99%
See 2 more Smart Citations